Tingkat Kecemasan antara Mendengar Pengumuman Pelaksanaan Ujian Secara Online dan Saat Ujian Dilaksanakan: Sebuah Studi Penelitian - Asmardi; Risnawati; M. Fikri Hamdani; Rohani (Indra institute Research & Publication, 2025)
Basically, in the current digital era, the use of online exams is increasingly common as an alternative method to assess students' knowledge and skills. However, these changes can also affect the level of anxiety experienced. Therefore, the researchers aim to determine the differences in students' anxiety levels when hearing the exam announcement and when the exam is conducted. The methodology used is a cross- sectional research design to collect data at two different stages: during the online exam announcement and during the actual online exam. The research participants consist of 24 students randomly selected from the population of students taking the online exam. The analysis results indicate that anxiety data in both groups are normally distributed and have homogeneous variance. Based on the results of the Independent Sample. T-Test, a significance value of 0.000 is obtained, indicating that there is a significant difference between the anxiety levels when hearing the exam announcement and during the actual online exam. This aligns with the decision-making basis: if the two-tailed significance value is less than 0.05, then there is a significant difference between the anxiety levels when hearing the exam announcement and during the actual online exam, and vice versa. Furthermore, in this study, gender was also examined, showing differences through tests conducted on anxiety causes such as limited understanding, time constraints, skills, and others. These findings are described in tables and graphs accordingly, and it was found that male students have higher anxiety levels during exams. Therefore, it can be concluded that there are differences in anxiety levels between hearing the exam announcement and during the actual exam.